2021
DOI: 10.3390/nu13010272
|View full text |Cite
|
Sign up to set email alerts
|

Association between Breakfast Skipping and Body Weight—A Systematic Review and Meta-Analysis of Observational Longitudinal Studies

Abstract: Globally, increasing rates of obesity are one of the most important health issues. The association between breakfast skipping and body weight is contradictory between cross-sectional and interventional studies. This systematic review and meta-analysis aims to summarize this association based on observational longitudinal studies. We included prospective studies on breakfast skipping and overweight/obesity or weight change in adults. The literature was searched until September 2020 in PubMed and Web of Science.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 105 publications
5
31
0
2
Order By: Relevance
“…The current findings are in line with a recent study published in the USA [12]. The association between breakfast skipping and BMI was discussed controversially (some found an association [13] while others found no relationship [14]). In the present survey, breakfast skipping was associated with a high BMI, in agreement with Gouda et al [15].…”
Section: Discussionsupporting
confidence: 92%
“…The current findings are in line with a recent study published in the USA [12]. The association between breakfast skipping and BMI was discussed controversially (some found an association [13] while others found no relationship [14]). In the present survey, breakfast skipping was associated with a high BMI, in agreement with Gouda et al [15].…”
Section: Discussionsupporting
confidence: 92%
“…Breakfast is the first meal of the day that ends the night fasting period and is deserving of special attention in the field of chrono-nutrition. Several observational studies of all ages reported an increased prevalence of OW/OB in people who skip breakfast [ 10 , 34 , 35 , 36 , 37 , 38 ], although these findings have been questioned in two recent meta-analyses on interventional studies in adults [ 11 , 39 ]. Our review demonstrates that breakfast skipping remains associated with a high prevalence of OW/OB and a worse nutritional profile in intervention RCTs and intervention longitudinal trials in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, breakfast consumption may hinder high concentrations of ghrelin and low concentrations of insulin, which induce hunger and eating [30]. These hormonal regulatory effects of breakfast consumption may translate to reduced appetite, lower caloric intake later throughout the day, improved weight control and lower T2D risk [28,30]; effects may be amplified when breakfast is skipped over 3 days per week compared to fewer days [31]. Additionally, consuming breakfast prior to lunch results in reduced glycemia and enhanced insulin after lunch, or "second meal phenomenon", due to enhanced beta-cell responsiveness at the second meal induced by the first meal [29].…”
Section: Evaluating the Role Of Time Of Eating Occasion On Biomarkers Of Glycemic Control In Patients With Diabetes (Pwd)mentioning
confidence: 99%
“…A potential reason for the increased T2D risk associated with higher meal frequency compared to lower meal frequency may be related to an increase in total caloric intake throughout the day due to overeating, consuming energy-dense foods, especially those high in refined carbohydrates, increased portion size, and decreased quality of foods [31,37]. Furthermore, large amount of nutrients in infrequent meals, such as fat and protein, could be responsible for a prominent increase of glucose-dependent insulinotropic polypeptide level, inducing enough increase in insulin after the meal to maintain a controlled glucose excursion [39].…”
Section: Does Meal Frequency or Number Of Times Eating Events Occurred Throughout A Day Effect Glycemic Control In Pwd?mentioning
confidence: 99%